PEMANFAATAN PUSAT SUMBER BELAJAR DALAM MENINGKATKAN HASIL BELAJAR - Imam Subqi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2016)
Learning Resource Centre has an important role in fostering quality learning outcomes. The learning process that occurs in the institutions of education and training is no longer possible to do with a lot of "feeding" the participants of his protégé. Learners must actively seeking information that is required, while the teacher (teacher or instructor) are obligated to give referrals, example and encouragement. In addition the demands will be the flexibility and leeway time and place to learn the longer. Information sources diversified need identified, prepared, developed, and utilized to facilitate the occurrence of the learning process. For that reason then organizing learning resources become large enough, especially in his position as a suport system in learning systems. Managing and organizing learning resources in an educational institution can be realized in the form of a learning resource center (PSB) with strategic measures in support of quality learning outcomes.Keywords : Utilization, learning resources and Learning Center\